(3EOGQI GdeSJTajGJs - (3CMeO eMeO(B, (3GdeYQjs ((3GdEScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 1998)
(3GdbhGYO GdYGeI ddEOGQI(B-(3EOGQI GdeSJTajGJ GdNGUI(B-(3GdJfXje GdOGNdj ddeSJTajGJ GdNGUI(B-(3GdYGedhf HGdeSJTai hJOQjHge(B-(3GdEJLGg GdMOjK ef EOGQI GdeSJTajGJ(B-(3Cge eTGcd EOGQI GdeSJTai GdNGUs
Keywords: (3GdEOGQIs; (3GdeSJTajGJs